Time participation of the continental tropical mass in the west part of Brazil´s south center - Borsato, Victor de Assunção; Mendonça, Francisco de Assis (Acta Scientiarum. Technology, 2014)
This study aimed at qualifying and quantifying the time spatialization of the continental Tropical mass participation in the state of weather in the west part of Brazil´s South Center, from 2002 to 2010, with special focus on 2003 and 2008, years of El Niño andLa Niña, considering that, beyond sparse studies, the region is close to this system´s center of action. As the origin of this air mass is continental, during its period of performance, days present low relative humidity, intense heating and lack of rain. In South Brazil, the performance is more intense in the hottest months, and on the west part of theWestCenterregion there are no studies. For this reason, it were chosen for this study the cities of Campo Mourão, in the State of Paraná, South of Brazil, and Cáceres, in the Sate of Mato Grosso, west part ofBrazil´sWestCenter. By analyzing the synoptic maps and satellite images, the participation of this system in a daily scale was quantified. The system showed itself more active for the region of Campo Mourão in the hottest months and for Cáceres during the winter. Â 